Pengembangan Website UMKM Pempek Madam Jambi Sebagai Media Informasi, Pemasaran dan Promosi - Febby Lutvianita; Ari Setiya Ningsih; Irfan Roihansyah Harahap; Tri Sherina; Bastian Wahyudi; Daniel Arsa; Dewi Lestari (Unity Academy, 2024)
The community service project aimed to assist Pempek Madam Jambi, a micro, small, and medium enterprise (MSME) in Jambi specializing in authentic Jambi-style pempek. The project addressed marketing and promotion challenges, as the MSME previously relied solely on Instagram and WhatsApp for sales and visibility. The initiative involved creating a website to serve as a marketing, promotional, and informational platform. The development process began with a needs analysis conducted through interviews with the business owner, followed by designing wireframes using Figma, website development via Canva Web, testing, and publishing the website. The website includes features such as a homepage, about us, menu listing, ordering platform, FAQ, articles, and SEO components to enhance product visibility. As a direct outcome, the website significantly improved the business’s digital presence and customer engagement. The project also conducted training involving five participants, including students, on digital marketing and website maintenance, enabling the MSME to sustain the platform independently. The initiative demonstrated a measurable impact, as online visibility increased by 87%, as indicated by user satisfaction feedback during website testing. This project serves as a scalable model for other MSMEs in Jambi, contributing to the broader agenda of MSME digital transformation in Indonesia.